Hepatitis E: A Newcomer to the Hepatitis Alphabet – Case Report and Review of the Literature - Karl Weiss; Louise Poirier; Sylvain Varin; Claire Beliveau; Michel Laverdière (Canadian Journal of Infectious Diseases)
The first Canadian case of hepatitis E is described in a patient who travelled to Asia for a six-month period and spent most of his time in India. Hepatitis E shares some similarities with hepatitis A, notably the mode of transmission and the absence of chronic course. However, a few important differences have been noted, including a higher mortality rate and a high fatality rate in pregnant women. Hepatitis E is very common in developing countries and should be suspected more often in individuals with gastrointestinal complaints returning from endemic areas.